OPTIMALISASI SUMBER DAYA MANUSIA MELALUI PELATIHAN TELEMARKETING DALAM MENINGKATKAN KUALITAS PELAYANAN DONATUR PADA YAYASAN SOSIAL - Herawati; Dadang; Supatmi; Iwan Supriyanto; Werna Hendri Nopayana; Mu'taeri; Fitri Rachmiati Sunarya (Haga : Jurnal Pengabdian Kepada Masyarakat, 2026)
Social foundations rely heavily on public trust and long-term donor relationships to sustain their programs. However, many foundations still experience limitations in donor communication, service management, and volunteer competence, reducing the effectiveness of donor engagement. This community service program aimed to strengthen human resource capacity through telemarketing training to improve the quality of donor services across three partner social foundations. The program employed a participatory approach consisting of preliminary observation, needs assessment, interactive training, simulation, mentoring, and evaluation. The activities involved administrators and volunteers who directly interacted with donors in daily fundraising services. The implementation focused on communication techniques, ethical donor services, relationship management, and practical telemarketing skills. The program results show that participants demonstrate improved communication competence, greater confidence in interacting with donors, and a better understanding of structured donor service management. The participating foundations also begin to adopt more systematic service practices and strengthen internal coordination in maintaining donor relationships. Overall, telemarketing training serves as an effective strategy for enhancing volunteer capacity while supporting sustainable donor engagement within social foundations. Continuous mentoring and periodic evaluation remain essential to maintain the long-term impact of the program. Keywords: human resource development1; telemarketing training2; donor service3; social foundation4; community service5;